Are human rights 'toothless' in Australian child protection matters? Perspectives of lawyers and social workers. (8th December 2022) - Walsh, Tamara; Healy, Karen; Venables, Jemma; Thompson, Kate
Abstract: Human rights law is in its infancy in Australia. Some states and territories have human rights legislation that requires government officials to take human rights into account in decision-making. However, there is very little Australian case law or commentary regarding the application of human rights law to child protection matters. In this article, we discuss the potential for human rights law to influence decision-making in child protection. We interviewed lawyers and social workers who support parents in child protection matters in the state of Queensland to determine whether they thought rights-based advocacy could bring about better outcomes for their clients. Whilst some social workers were optimistic about the potential for human rights advocacy to improve outcomes for parents, lawyers generally believed that human rights law was unlikely to assist. Jurisprudence from other jurisdictions demonstrates that human rights arguments can influence outcomes in child protection matters, so additional human rights training may be needed for lawyers and judicial officers in Australia to encourage consideration of human rights in child protection cases.